PERBEDAAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA DENGAN METODE TEAM QUIZ DAN METODE INDIVIDUAL QUIZ PADA MATERI BARISAN DAN DERET DI KELAS - Halawa, Matius (Afore : Jurnal Pendidikan Matematika, 2024)
This research was motivated by the team quiz method and the individual student quiz method being less effective. The purpose of this research is to find out whether there is a difference in students' mathematical problem solving abilities using the Team Quiz and Individual Quiz methods on sequence and series material in Class X of SMK Negeri 1 Lolowa'u. The type of research used is quantitative research. The population in this study was class X with a total of 55 students. The research instrument used was a test of mathematical problem solving abilities using the team quiz method and the individual quiz method. The results of the research stated that in experimental class 1, by carrying out the initial test, the average learning outcome was 52.33 and in experimental class 2, the average learning outcome was 50.01. Meanwhile, in the final test in experimental class 1, the average learning result was 72.94 and in experimental class 2, the average learning result was 71.01. So, there are differences in students' mathematical problem solving abilities using the Team Quiz and Individual Quiz methods. So it can be concluded that applying the Team Quiz and Individual Quiz methods has a great influence on the learning outcomes of class X students at SMK Negeri 1 Lolowa'u. The suggestion put forward by researchers is that teachers should use team quiz and individual quiz methods in learning in order to increase active student participation in learning that takes place in class, as well as serve as a guide or reference for every reader or future researcher, but pay attention to weaknesses in order to obtain appropriate solutions. even better.